Using the Penetration Testing Execution Standard Method (PTES) for Wireless Network Security Analysis - Ridwan Ridwan (Green Publisher, 2024)
As more people utilize the internet, network security has grown in importance. The internet has an impact on practically every part of life, including the employment. Located in the Tambun Utara District of Bekasi Regency, the Setia Mekar Village Hall office is a public service location. It now relies on a single wireless access point to connect to the internet and uses Wireless Local Area Network (WLAN) technology to meet the demands of the community for a variety of internet-related reasons, including administrative and other services. In order to prevent numerous criminal risks, wireless networks need to be well-secured. As such, a security analysis of the network utilizing the Penetration Testing Execution Standard (PTES) method a framework or set of guidelines used as a reference for conducting network penetration testing is required. The types of attacks that circumvent MAC authentication and ARP spoofing were tested five times using a Kali Linux virtual machine. The results showed that although there were three failures and two successes in cracking the encryption. The test findings indicate that the wireless network security system is fairly secure; however, in order to bolster security and reduce the likelihood of crime, a number of changes to the network architecture and configuration system are required.